The Effect of Immunization Counseling with Discussion Method on Increasing Mothers' Knowledge and Attitudes about Basic Immunization in Infants Aged 0-12 Months - Faridah Faridah; Rani Safitri (Jurnal Siti Rufaidah, 2025)
Mothers' knowledge and attitudes play a crucial role in the success of the basic immunization program for infants. This study aimed to analyze the effect of counseling using the discussion method on improving mothers' knowledge and attitudes regarding basic immunization for infants aged 0-12 months. The study used a pre-experimental one-group pretest-posttest design with a sample of 30 mothers selected through purposive sampling. The research instrument consisted of a knowledge and attitude questionnaire that had been tested for validity and reliability. The intervention was conducted through a 60-minute focus group discussion, which included an initial presentation, active discussion, scientific clarification, and conclusion drawing. The results showed a significant increase in knowledge, from an average score of 9.13 to 13.47 (p = 0.000), and in attitudes, from an average score of 31.50 to 41.30 (p = 0.000). The distribution of categories also showed a significant shift towards better knowledge and attitudes after the intervention. This study concluded that the discussion method was effective in improving mothers' understanding and forming positive attitudes towards basic immunization, making it worthy of recommendation as an educational method in health care facilities.